Menelaah Pengelolaan Keuangan Sekaa Santhi atas Pendapatan Batu-Batu Uleman di Banjar Penarungan - Wati, Luh Putu Erlina Ariya; Dewi, Luh Gede Kusuma (Universitas Pendidikan Ganesha, 2021)
Sekaa santhi is a non-profit organization that auspices of the banjar. This study aims to find out:(1) how accountability, community participation and justice in the financial management of the Sekaa Santhi Eka Dharma Saba trough to batu-batu and uleman income. The research was conducted at the Sekaa Santhi Eka Dharma Saba, Penarukan Disrict, Buleleng Regency. This study using a qualitative method. The data used in this study are primary data and secondary data. The result this study is (1) accountability has been implemented by making simple record in a note book for batu-batu uleman income and also expenditure, then community participation has been implemented by assigning members the task of managing finances during Genitri activities and justice has been implemented that all member known a financial record.